Alignment of the Hindfoot Following Total Knee Arthroplasty: A Systematic Review. Issue 1 (January 2022) - Azam, Mohammad; Butler, James J.; Mercer, Nathaniel P.; Hurley, Eoghan T.; Kennedy, John G.
Category: Ankle; Hindfoot Introduction/Purpose: The purpose of this systematic review was to evaluate changes in the alignment of the hindfoot following total knee arthroplasty (TKA), subjective clinical outcomes following surgical intervention and to analyze the level of evidence (LOE) and quality of evidence (QoE) of the included studies. Methods: MEDLINE, EMBASE, and Cochrane Library databases were systematically reviewed in accordance with the Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA) guidelines. Studies reporting changes in the postoperative alignment of the hindfoot following TKA were included. The level and quality of evidence were recorded and assessed. Results: Eleven studies with a total of 1142 patients (1358 knees) met the inclusion/exclusion criteria. Six studies were of level of evidence II and 5 studies were of level of evidence III. Patients with preoperative varus knee deformity and valgus hindfoot deformity demonstrated improvement in hindfoot alignment post-TKA. Patients with preoperative varus knee deformity and varus hindfoot deformity demonstrated no improvement in hindfoot alignment following TKA. Twelve different radiographic parameters were used to measure the alignment of the hindfoot across the included studies, with the tibio-calcaneal angle (TCA) most frequently utilized (27.3%). Conclusion: This systematic review demonstrated that the hindfoot may display compensatory changes in alignment following total knee arthroplasty in patients with knee osteoarthritis. However, the marked heterogeneity between the included studies and poor quality of evidence limits any meaningful cross-sectional comparisons between studies. Further, well-designed studies are necessary to determine the changes and outcomes of hindfoot alignment following total knee arthroplasty.